Evaluation of non pesticide management practices against sucking pests of black gram under agency tracts of East Godavari district, Andhra Pradesh - Rao, V Govardhan; VenkataRamana, P (Indian Journal of Plant Protection, 2020)
Non Pesticide Management (NPM) practices suggested by ITKs revealedthat application of herbal extracts signifcantly reduced the sucking pest’s population (per leaf/plant) by aphids (2.1), leafhopper (2.0) and whiteﬂy (1.7),disease incidence of Yellow Mosaic Virus (5.3) with high yielding variety LBG-752 in demo. 7.10 q/ha in farmer’spractice.The demo feld experiments resulted in higher C: B ratio of 1:2.15 as compared to 1:1.5 in the farmer’s practices by reducing total avoidableloss (4.8 kg)and percent Yield increase over farmer practice (67.6) respectively.